2022
DOI: 10.1038/s41586-022-05160-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical amputation of a limb 31,000 years ago in Borneo

Abstract: The prevailing view regarding the evolution of medicine is that the emergence of settled agricultural societies around 10,000 years ago (the Neolithic Revolution) gave rise to a host of health problems that had previously been unknown among non-sedentary foraging populations, stimulating the first major innovations in prehistoric medical practices1,2. Such changes included the development of more advanced surgical procedures, with the oldest known indication of an ‘operation’ formerly thought to have consisted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
0
19
0
4
Order By: Relevance
“…The Late Pleistocene population increase occurs during a period associated with complex and diverse material culture, new technologies and likely role specialization [ 171 ], e.g. a surgical amputation of a limb dates from approximately 31 ka in Borneo [ 182 ]. We also see the emergence of relatively sedentary hunter–gatherer societies with emergent inequality in resource-rich areas.…”
Section: Discussionmentioning
confidence: 99%
“…The Late Pleistocene population increase occurs during a period associated with complex and diverse material culture, new technologies and likely role specialization [ 171 ], e.g. a surgical amputation of a limb dates from approximately 31 ka in Borneo [ 182 ]. We also see the emergence of relatively sedentary hunter–gatherer societies with emergent inequality in resource-rich areas.…”
Section: Discussionmentioning
confidence: 99%
“…Chile is particularly vulnerable to the effects of global warming, research has shown. In northern Chile, food insecurity and water scarcity have become major issues 1 .…”
mentioning
confidence: 99%
“…In central Chile, longer and more frequent heatwaves have been taking a toll: since 2010, a rainfall deficit has created a 'megadrought' there, affecting the livelihoods of more than ten million people 1 . And in the southern region, Patagonia, the number of wildfires has grown at an alarming rate 2 .…”
mentioning
confidence: 99%
“…
ishing gear from just five regions could account for most of the floating plastic debris in the 'North Pacific garbage patch', a vast swathe of the North Pacific Ocean that holds tens of thousands of tonnes of plastic.A study published on 1 September in Scientific Reports found that up to 86% of the large pieces of floating plastic in the garbage patch are items that were abandoned, lost or discarded by fishing vessels (L. Lebreton et al Sci. Rep. 12, 12666;2022). The finding is counterintuitive, given that most marine plas tic makes its way into the ocean through rivers.These findings "change our understanding of the sources of plastic in the North Pacific garbage patch", says Matthias Egger, an ocean plastic researcher at the Ocean Cleanup, a non profit organization based in Rotterdam, the Netherlands, that develops techniques for removing plastic from the ocean.
…”
mentioning
confidence: 99%
“…A study published on 1 September in Scientific Reports found that up to 86% of the large pieces of floating plastic in the garbage patch are items that were abandoned, lost or discarded by fishing vessels (L. Lebreton et al Sci. Rep. 12, 12666;2022). The finding is counterintuitive, given that most marine plas tic makes its way into the ocean through rivers.…”
mentioning
confidence: 99%